Genetic Diversity and Demography of Skipjack Tuna (Katsuwonus pelamis) In Southern and Western Part of Indonesian Waters - Irwan Jatmiko; Raymon Rahmanov Zedta; Maya Agustina; Bram Setyadji (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2019)
Skipjack tuna (Katsuwonus pelamis) is highly migratory species that spread from trophic and sub trophic waters. This species can be found in Atlantic, Indian and Pacific oceans. The genetic information of highly migratory species like skipjack tuna is important to support the sustainability of the fisheries. The objectives of this study are to gain information genetic diversity and population structure of exploited species and to understand the population kinship in Indonesian waters. Tissue samples were collected from six locations, i.e.: Sibolga (North Sumatera), Padang (West Sumatera), Binuangeun (Banten), Pacitan (East Java), Lombok (West Nusa Tenggara) and Kupang (East Nusa Tenggara). Microsatellite analysis was done in this study consisting of extraction, purification, polymerase chain reaction (PCR) amplification and electrophoresis. Three loci used for the analysis i.e.: UTD 172, UTD 523 and UTD 535. The results showed that there are two groups from six locations i.e.: group 1: Sibolga and Padang; group 2: Binuangeun, Pacitan Lombok and Kupang. The variance among these two groups is 0.066 with variance 5.441%. This finding in line with Indonesian Fisheries Management Area of 572 (west of Sumatera waters) and 573 (south of Java waters). However, as highly migratory species across nations, the management strategy for skipjack tuna needs collaboration among countries through regional fisheries management authority like Indian Ocean Tuna Commission (IOTC).